2013
DOI: 10.1111/ppl.12088
|View full text |Cite
|
Sign up to set email alerts
|

Chromium stress response effect on signal transduction and expression of signaling genes in rice

Abstract: Hexavalent chromium [Cr(VI)] is a non-essential metal for normal plants and is toxic to plants at high concentrations. However, signaling pathways and molecular mechanisms of its action on cell function and gene expression remain elusive. In this study, we found that Cr(VI) induced endogenous reactive oxygen species (ROS) generation and Ca(2+) accumulation and activated NADPH oxidase and calcium-dependent protein kinase. We investigated global transcriptional changes in rice roots by microarray analysis. Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 92 publications
(98 reference statements)
3
51
0
1
Order By: Relevance
“…The Cu-inducible expression of the ACS genes in potato (Solanum tuberosum) and the accumulation of the ACS transcripts in different varieties of tobacco (Nicotiana tabacum) have been reported . Recently, transcriptome analysis of chromium-treated rice (Oryza sativa) roots also indicated enhanced expression of four ethylene biosynthesis-related genes (ACS1, ACS2, ACO4, and ACO5), suggesting the participation of ethylene in chromium signaling in rice (Steffens, 2014;Trinh et al, 2014). These findings together demonstrated that ethylene is enhanced in response to various Figure 1.…”
Section: Ethylene and Plant Responses To Hm Stresssupporting
confidence: 62%
“…The Cu-inducible expression of the ACS genes in potato (Solanum tuberosum) and the accumulation of the ACS transcripts in different varieties of tobacco (Nicotiana tabacum) have been reported . Recently, transcriptome analysis of chromium-treated rice (Oryza sativa) roots also indicated enhanced expression of four ethylene biosynthesis-related genes (ACS1, ACS2, ACO4, and ACO5), suggesting the participation of ethylene in chromium signaling in rice (Steffens, 2014;Trinh et al, 2014). These findings together demonstrated that ethylene is enhanced in response to various Figure 1.…”
Section: Ethylene and Plant Responses To Hm Stresssupporting
confidence: 62%
“…Total RNA extraction involved use of the RNeasy Plant Mini kit (QIAGEN, Hilden, Germany) following the manufacturer’s instructions with some modifications. Semi-quantitative RT-PCR and quantitative RT-PCR (qRT-PCR) reactions were performed as previously described [13]. Relative quantification of specific mRNA levels was analyzed using the cycle threshold (Ct) (2 −ΔΔCt ) method [14].…”
Section: Methodsmentioning
confidence: 99%
“…; Trinh et al . ). Exogenous ABA application has been reported to reduce transpiration, leading to reduced Zn translocation from the soil to the aerial parts of plants, and to enhance the heavy metal tolerance of plants via defence priming in plants (Hsu & Kao 2003, 2005, 2008; Zhao et al .…”
Section: Introductionmentioning
confidence: 97%
“…ABA is involved in defence priming in plants (Luo et al 2009) and can activate antioxidative defence systems that contribute to the alleviation of heavy metal toxicity (Sharma & Kumar 2002;Wang et al 2013). Moreover, elevated ABA levels in plants can trigger the signalling cascades downstream of phytohormones, such as salicylic acid (SA) and auxin (IAA), which may also mitigate heavy metal-induced toxicity (Stroinski et al 2010;Noriega et al 2012;Disante et al 2014;Trinh et al 2014). Exogenous ABA application has been reported to reduce transpiration, leading to reduced Zn translocation from the soil to the aerial parts of plants, and to enhance the heavy metal tolerance of plants via defence priming in plants (Hsu & Kao 2003, 2008Zhao et al 2009).…”
Section: Introductionmentioning
confidence: 99%